Measuring ethnic identity and its impact on economic behavior - Amelie F. Constant; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The paper advocates for a new measure of the ethnic identity of migrants, models its determinants and explores its explanatory power for various types of their economic performance. The ethnosizer, a measure of the intensity of a person's ethnic identity, is constructed from information on the following elements: language, culture, societal interaction, history of migration, and ethnic self-identification. A two-dimensional concept of the ethnosizer classifies migrants into four states: integration, assimilation, separation and marginalization. The ethnosizer largely depends on pre-migration characteristics. Empirical evidence studying economic behavior like work participation, earnings and housing decisions demonstrates the significant relevance of ethnic identity for economic outcomes.
Keywords: F22; J15; J16; Z10; 330; Ethnicity; ethnic identity; acculturation; migrant assimilation; migrant integration; work; cultural economics; Migranten; Ethnische Gruppe; Kulturpsychologie; Soziale Integration; Wirtschaftsethnologie; Deutschland